X‐Ray Amorphous Sulfur‐Bearing Phases in Sedimentary Rocks of Gale Crater, Mars. Issue 5 (25th May 2022) - Smith, R. J.; McLennan, S. M.; Sutter, B.; Rampe, E. B.; Dehouck, E.; Siebach, K. L.; Horgan, B. H. N.; Sun, V.; McAdam, A.; Mangold, N.; Vaniman, D.; Salvatore, M.; et al.
Abstract: The Curiosity rover in Gale crater is investigating a mineral transition observed from orbit—an older "clay unit" to a younger "sulfate unit"—hypothesized to reflect the aridification of Mars' climate. Below this transition, the rover detected crystalline Ca‐sulfates with minor Fe‐sulfates but also found that some fraction of a rock's bulk SO3 is often in the poorly constrained X‐ray amorphous component. Here, we characterize the abundances and compositions of the X‐ray amorphous sulfur‐bearing phases in 19 drilled samples using a mass balance approach, and in a subset of 5 samples using evolved SO2 gas measured using the SAM instrument. We find that ∼20–90 wt% of a sample's bulk SO3 is in the X‐ray amorphous state and that X‐ray amorphous sulfur‐bearing phase compositions are consistent with mixtures of Mg‐S, Fe‐S, and possibly Ca‐S phases, likely sulfates or sulfites. These phases reside in the bedrock, perhaps as cementing agents deposited with detrital sediments or during early diagenesis, and in diagenetic alteration halos deposited after lithification during late diagenesis. The likely presence of highly soluble Mg‐sulfates in the rocks suggests negligible fluid flow through the bedrock post‐Mg‐sulfate deposition. The X‐ray amorphous sulfur‐bearing phases probably became amorphous through dehydration in the current Martian atmosphere or inside the CheMin instrument. X‐ray amorphous sulfur‐bearing materials likely contribute to orbital spectral detections of sulfates, and so our results help form multiple hypotheses to be tested in the sulfate unit and are important for understanding the evolution of the Martian surface environment at Gale crater. Plain Language Summary: The Curiosity rover in Gale crater, Mars is investigating a mineral transition observed from orbit—older clay‐rich to younger sulfur‐rich rocks—that likely reflects a change from a wetter to a drier Martian climate. In many of the sedimentary rocks investigated below the mineral transition, rover instruments identified different sulfur‐bearing phase assemblages. Inconsistencies indicate the presence of poorly constrained sulfur‐bearing phases that are undetected by the CheMin X‐ray diffraction instrument (X‐ray amorphous). To fully appreciate the significance of the transition to more sulfate‐rich rocks, we investigate the abundance and composition of X‐ray amorphous sulfur‐bearing phases at 19 drill sites below the transition. We find that most rocks have large fractions of X‐ray amorphous sulfur‐bearing phases that are likely mixtures of Mg‐, Fe‐, and possibly Ca‐sulfates or sulfites. In some rocks, these sulfur‐bearing phases might have precipitated from solutions delivered to the lake early on, acting to cement sediment grains. In other locations, X‐ray amorphous sulfur‐bearing phases are associated with zones where fluids altered the rocks long after they were cemented. These results help form multiple hypotheses to be tested in the sulfate‐rich rock unit and are important for understanding the evolution of the Martian surface environment at Gale crater. Key Points: A large percentage of the bulk SO3 in Gale crater sedimentary rocks is in the X‐ray amorphous state (20%–90%) X‐ray amorphous S‐bearing phases are likely mixtures of Mg, Fe, Ca, and other cation sulfates present as cement and in diagenetic features In situ detections of X‐ray amorphous SO3 likely contribute to orbital spectral detections of sulfates in lower Mount Sharp